Respuesta :
Answer: The prove is mentioned below.
Step-by-step explanation:
Here the given functions are,
[tex]f(x)=\frac{x-7}{x+3}[/tex]
[tex]g(x)=\frac{-3x-7}{x-1}[/tex]
We have to prove that: f(g(x)) = x and g(f(x)) = x.
Since [tex]f(g(x))= \frac{(-3x-7)/(x-1) -1}{(-3x-7)/(x-1) +3}[/tex]
⇒[tex]f(g(x))= \frac{-3x-7-7x+7}{-3x-7+3x-3}[/tex]
⇒[tex]f(g(x))= \frac{-4x}{-4}[/tex]
⇒[tex]f(g(x))= x[/tex]
Now, [tex]g(f(x))= \frac{-3(x-7)/(x+3) -7}{(x-7)/(x+3) -1}[/tex]
⇒[tex]g(f(x))= \frac{-3x+21-7x-21}{x-7-x-3}[/tex]
⇒[tex]g(f(x))= \frac{-10x}{-10}[/tex]
⇒[tex]g(f(x))= x[/tex]
Answer with Step-by-step explanation:
We are given that
[tex]f(x)=\frac{x-7}{x+3}[/tex]
[tex]g(x)=\frac{-3x-7}{x-1}[/tex]
We have to confirm that f and g are inverses by showing that f(g(x))=x=g(f(x))
[tex]f(g(x))=f(\frac{-3x-7}{x-1})[/tex]
[tex]f(g(x))=\frac{\frac{-3x-7}{x-1}-7}{\frac{-3x-7}{x-1}+3}[/tex]
[tex]f(g(x))=\frac{\frac{-3x-7-7x+7}{x-1}}{\frac{-3x-7+3x-3}{x-1}}[/tex]
[tex]f(g(x))=\frac{-10x}{x-1}\times \frac{x-1}{-10}[/tex]
[tex]f(g(x))=x[/tex]
[tex]g(f(x))=g(\frac{x-7}{x+3})[/tex]
[tex]g(f(x))=\frac{-3(\frac{x-7}{x+3})-7}{\frac{x-7}{x+3}-1}[/tex]
[tex]g(f(x))=\frac{\frac{-3x+21-7x-21}{x+3}}{\frac{x-7-x-3}{x+3}}[/tex]
[tex]g(f(x))=\frac{\frac{-10x}{x+3}}{\frac{-10}{x+3}}[/tex]
[tex]g(f(x))=\frac{-10x}{x+3}\times \frac{x+3}{-10}=x[/tex]
Hence, f(g(x))=g(f(x))=x
Therefore, f and g are inverses.